Community Compliance with Fishing Ordinances in the Coastal Municipalities of Bohol Province - Justeofino Hinlayagan; Princess Beronica Esteban; Grace Alincastre; Reynante Malvar; Johnnyboy Itcay; Ian Christian Filipino; Joel Pagkaliwangan; Mhel Jeric De Torres; Antonio Flores Jr.; Elizabeth Villa Villa (Future Science / FSH-PH Publications, 2026)
Illegal, unreported, and unregulated (IUU) fishing continues to threaten marine biodiversity, coastal food security, and local governance across the Philippine archipelago. While national laws such as Republic Act No. 10654 outline strict penalties for destructive fishing practices, localized enforcement challenges continue to be significant at the municipal level, where daily compliance and implementation are directly tested. Employing a quantitative descriptive-correlational research design, this study targeted various stakeholders across the 30 coastal municipalities of Bohol. Data were collected via a validated structured survey questionnaire administered to local chief executives; Municipal Environment and Natural Resources Office (MENRO) personnel; military/uniformed law enforcement officers (via convenience sampling); and community residents (via proportionate selection or complete enumeration). While institutional enhancements like the Police Environment Desk exist, actual ordinance compliance is heavily constrained by operational deficiencies—including inadequate patrol boats, insufficient fuel, limited manpower, and fragmented multi-agency communication—alongside economic pressures and awareness gaps among small-scale fisherfolk. Effective local fisheries management relies on an interdependent ecosystem of legal authority, enforcement capability, and civic alignment. Simply enacting ordinances is insufficient to deter violations. To bridge these compliance and implementation gaps, the study proposes a responsive, multi-tiered action plan focused on strengthening local seaborne patrol visibility, upgrading logistical support for first responders, solidifying inter-agency collaboration channels, and enhancing community-driven conservation education.